Rapid preparation of alpha-FeOOH and alpha-Fe2O3 nanostructures by microwave heating and their application in electrochemical sensors - Marinho, J. Z.; Montes, R. H. O.; Moura, A. P. de [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP]; Munoz, R. A. A.; Lima, R. C. (Elsevier B.V., 2014)
alpha-FeOOH (goethite) and alpha-Fe2O3 (hematite) nanostructures have been successfully synthesized using the microwave-assisted hydrothermal (MAH) method and by the rapid burning in a microwave oven of the as-prepared goethite, respectively. The orthorhombic alpha-FeOOH to rhombohedral alpha-Fe2O3 structural transformation was observed by X-ray diffraction (XRD) and Raman spectroscopy results. Plates-like alpha-FeOOH prepared in 2 min and rounded and quasi-octahedral shaped alpha-Fe2O3 particles obtained in 10 min were observed using field emission gun scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). The use of microwave heating allowed iron oxides to be prepared with shorter reaction times when compared to other synthesis methods. alpha-FeOOH nanoplates were incorporated into graphite-composite electrodes, which presented electrocatalytic properties towards the electrochemical oxidation of ascorbic acid in comparison with unmodified electrodes. This result demonstrates that such alpha-FeOOH nanostructures are very promising chemical modifiers for the development of improved electrochemical sensors. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Chemical synthesis; X-ray diffraction; Electron microscopy; Electrochemical properties